Autophagy and the Bone Marrow Microenvironment: A Review of Protective Factors in the Development and Maintenance of Multiple Myeloma - Hamedi, Kamron R.; Harmon, Katrina A.; Goodwin, Richard L.; Arce, Sergio (Frontiers in Immunology, 2022)
The role of the unfolded protein response (UPR) in plasma cells (PC) and their malignant multiple myeloma (MM) counterparts is a well described area of research. The importance of autophagy in these cells, as well as the interplay between autophagy and the UPR system, has also been well studied. In this review, we will discuss the relationship between these two cellular responses and how they can be utilized in MM to account for the high levels of monoclonal immunoglobulin (Ig) protein synthesis that is characteristic of this disease. Interactions between MM cells and the bone marrow (BM) microenvironment and how MM cells utilize the UPR/autophagy pathway for their survival. These interacting pathways form the foundation for the mechanism of action for bortezomib, a proteasome inhibitor used to modify the progression of MM, and the eventual drug resistance that MM cells develop. One important resistance pathway implicated in MM progression is caspase 10 which attenuates autophagy to maintain its prosurvival function and avoid cell death. We lay a groundwork for future research including 3D in vitro models for better disease monitoring and personalized treatment. We also highlight pathways involved in MM cell survival and drug resistance that could be used as new targets for effective treatment.